A Case of Hypercalcemia in an Immunocompetent Patient with Disseminated Mycobacterium marinum Infection with a Rain Barrel as the Most Likely Primary Source - Wendy Uijtendaal (SMC MEDIA SRL, 2021)
Infection with Mycobacterium marinum is common in fish, and so human infection usually arises from contact with contaminated water or fish. A solitary papulonodular lesion on a finger or hand is the typical presentation. Disseminated infections are rare and mostly seen in immunocompromised patients.